TEACHING SPEAKING OF ENGLISH AS A FOREIGN LANGUAGE: PROBLEMS AND SOLUTIONS - noprianus tammu batang (Teaching English as a Foreign Language Overseas Journal, 2016)
This article is aimed to describe what teaching speaking English is and the problemsfaced by the teachers and students of English as a Foreign Language (EFL). Speakingis one of important skills that need to be acquired by students of EFL becausesometimes success is measured in terms of the ability to carry out a conversation inthe (target) language. Teaching students to speak English might become a problemfor some EFL teachers. This is not an easy task for teachers to make their studentsspeak because the language is not spoken in the community and also they have lessexposure to the language itself. Just as Harmer said (1998:52), to facilitate studentswith the ‘new’ language, teachers should have students exposed to the language,understand its meaning, understand its form (how it is constructed) and practice it.Therefore, in order to encourage their students to speak, teachers must do somethingdifferent than they usually do in teaching other skills. Teachers can create moreenjoyable speaking class by doing some activities such as role-play, discussion orsome kinds of games to promote students’ speaking ability.